Key factors of the competitiveness of healthcare entities - Sikora, Tomasz; Kanecki, Krzysztof; Sikora, Agnieszka; Bogdan, Magdalena (Journal of Education, Health and Sport, 2021)
Introduction: The healthcare sector, like other sectors of the economy, is based on competition. Due to the uniqueness of the services provided (involving saving human health and life), the competitiveness of healthcare entities differs from the typical free market. Purpose: The aim of the study was to identify the factors of competitiveness of healthcare entities in four distinguished areas of competitiveness of enterprises - external factors (macro- and micro-environment) and internal factors (resources and assets). Results: Macro-environment factors were grouped into: political-legal, economic, social, technological, and demographic. Micro-environment was divided into: consumers, competitors (considering their intensity and entry barriers), and suppliers. Resources were divided into: financial assets, room infrastructure, and equipment facilities. Assets, on the other hand, were characterized based on the elements of the organization’s system, determining their efficiency – strategy, styles, competencies, employees, structure, and organization’s culture. Conclusions: The review and systematization of factors influencing the competitiveness of healthcare entities enables to assess their competitive potential in the context of individual areas and key success factors.